Fluorescent zinc and copper complexes for detection of adrafinil in paper-based microfluidic devices. Issue 53 (13th June 2016) - Caglayan, Mehmet Gokhan; Sheykhi, Sara; Mosca, Lorenzo; Anzenbacher, Pavel
Abstract : Zn(ii ) and Cu(ii ) complexes are used in the recognition and sensing of adrafinil through an easy-to-detect fluorescence response. Abstract : Recognition of electroneutral Lewis bases and anions in aqueous media is extremely difficult. We show that fluorescent coordinatively unsaturated metal complexes can recognize various Lewis bases while providing an easy-to-detect fluorescence response. This approach is applied to the detection of adrafinil, a banned performance-enhancing drug.